Estrategias comunicacionales de inclusión periodística de personas con discapacidad - Aparicio Zambrano, Eduardo (2022)
The research was directed to the communicational analysis of the newscasts of two of the most important media in the country, Televistazo (Ecuavisa) and El Noticiero (TC Televisión) and it was established to search for the strategies implemented for the accessibility of information for people with sensory disabilities (visual and hearing). The research, which has a mixed approach (quantitative and qualitative), is descriptive, explanatory, documentary, and field research. The research techniques used were the survey, interview and observation sheets. Professionals and actors related to the topic were interviewed. In addition, the survey was applied under a non-probabilistic intentional sampling to 25 visually impaired people from the "Ciegos y amigos de Los ciegos" center in the city of Guayaquil.